Effects of Different Doses of Biochar and Zinc Phosphate Applications on the Development of Canola Plants - BEYYAVAŞ , Vedat; CUN, Suat; SAKİN , Erdal and TURHAN , Dilek (MAS Journal of Applied Sciences, 2024)
In agriculture, many organic compounds are used as organic fertilizers to maintain plant production. Biochar organic soil amendments are commonly recommended for improving problematic soils due to their environmental friendliness, efficiency, and economic viability. In this experiment, canola (rapeseed) was used as the plant material. Zinc phosphate and cotton stalk biochar at different doses were used as nutrient sources. The study was conducted using a randomized block design with 3 replications, and plastic pots were used. All treatments were applied along with the planting process. In the control group, no treatment was applied, while in the second treatment, only 0.8 g of zinc phosphate was added to the soil, and the soil was mixed thoroughly. In other treatments, cotton stalk biochar was applied along with 0.8 g of zinc phosphate in the following doses: 1.2 g/pot, 2.4 g pot-1, and 3.6 g pot-1. The results showed that the application of zinc phosphate and zinc phosphate + biochar increased the canola plant yield in relation to increasing doses. Specifically, with 0.8 g zinc phosphate, the increase was 6.40%, with 0.8 g zinc phosphate + 1.2 g biochar it was 14.57%, with 0.8 g zinc phosphate + 2.4 g biochar it was 20.21%, and with 0.8 g zinc phosphate + 3.6 g biochar, the increase reached 25.75%. The highest increase was observed with the application of 0.8 g zinc phosphate + 3.6 g biochar, while the lowest increase was observed with 0.8 g zinc phosphate. The study demonstrated that the application of biochar positively contributed to the plant parameters.